The Role of Brand Image in Mediating the Influence of Celebrity Endorsement and e-WOM on Purchase Intention of Skintific Skincare Products - Cynthia Pangrestu; Liem Bambang Sugiyanto (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study aims to analyse the role of brand image in mediating the influence of celebrity endorsement and e-WOM on purchase intention for Skintific skincare products on the Shopee platform. Specifically, the study examines the use of Mahalini as a celebrity endorser who actively promotes Skintific, as well as how consumers who have been exposed to these promotions and have read online reviews form brand perceptions prior to making a purchase decision. This study employs the Stimulus–Organism–Response (SOR) theoretical framework, in which celebrity endorsement and e-WOM function as the stimulus, brand image as the internal psychological state (organism), and purchase intention as the response. A quantitative approach is adopted, with data analysed using Structural Equation Modelling (SEM) based on Partial Least Squares (PLS). Data were collected through an online questionnaire administered to 275 Shopee users domiciled in DKI Jakarta who had purchased Skintific products, been exposed to promotions by Mahalini, and read consumer reviews. Data analysis was conducted using SmartPLS 3 to test both the measurement model and the structural model. The results indicate that celebrity endorsement by Mahalini and e-WOM each have a positive and significant effect on both brand image and purchase intention. Furthermore, brand image is confirmed to significantly mediate the relationship between celebrity endorsement and e-WOM and purchase intention.